Molecular characterization of pre-extensive drug resistant Mycobacterium tuberculosis in Northeast Brazil - Campelo, Thales Alves (2020)
In Fortaleza, the capital of Ceara State, Brazil, the detection rate of tuberculosis (TB) in 2018 was 65.5/100,000 inhabitants with a cure rate of 59.1%, which is higher than the country average. This study investigated the risk factors associated with drug-resistant tuberculosis (DR-TB) and identified the drug-resistance phenotype and resistance-conferring mutations. The geographic distribution of DR-TB in Fortaleza, Brazil, was also determined. From March 2017 to February 2018, 41 DR-TB isolates and 69 drug-susceptible pulmonary TB isolates were obtained from patients seen at a referral hospital in Fortaleza, Brazil. Samples were subjected to phenotypic and genetic analysis of resistance; the spatial distribution of the participants was also analyzed. Primary resistance was high (50.9%) among participants. The following risk factors for DR were identified: being female (p = 0.03), having diabetes (p < 0.01), history of previous TB disease (p < 0.01), and the number of intra-domiciliary contacts (p < 0.01). Analysis by multiplex allele-specific polymerase chain reaction detected mutations in the genes katG (65.8%), rpoB (43.9%), inhA promoter (14.6%), and gyrA (9.8%). Sequencing identified mutations in the the genes katG (75.6%), inhA promoter (19.5%), rpoB (85.4%), and gyrA (100%). There was no mutation in the rrs gene. Spatial analysis showed DR-TB isolates distributed in areas of low socioeconomic status in the city of Fortaleza. Our results emphasized the importance of detecting resistance to TB drugs. The resistance found in the gene gyrA is of concern due to the high number of pre-extensive DR-TB cases in Fortaleza.